Past imperfect - Fellowes, Julian (London : Phoenix, 2009)
Wishing to track down a past girlfriend who claims he had fathered her child, the rich and dying Damian Baxter contacts an old friend from his days at Cambridge. The search takes the narrator back to 1960s London, where everything is changing--just not always quite as expected.
Keywords: Upper class -- Fiction -- England; London (England) -- Fiction. -- Social life and customs -- 20th century